Ejecución de la reparación integral en materia de tránsito establecida en sentencia condenatoria bajo las reglas del COIP y del COGEP - Donoso Rivas, William Ricardo (2021)
Comprehensive reparation, as a basic concept of constitutional decisions, has had multiple references, mainly from international human rights law, given its main object of protection, human dignity, which have been assimilated at the normative and jurisprudential level, by the Ecuadorian State from the change of constitutional model. The basic principles on the right of victims of manifest violations of international human rights and international humanitarian law to file appeals and obtain reparations, which were approved by the United Nations General Assembly, fifteen years later, establish various forms of reparation, which can be summarized as: restitution, compensation, rehabilitation, satisfaction and guarantees of non-repetition.........